2018
DOI: 10.1002/aoc.4398
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of CuS and ZnO/Zn(OH)2 nanoparticles and their evaluation for in vitro antibacterial and antifungal activities

Abstract: In this study, the copper sulfide nanoparticles (CuS‐NPs) and the zinc oxide/zinc hydroxide nanoparticles ((ZnO/Zn(OH)2‐NPs) were synthesized by a simple and low‐cost method, and the synthesized nanoparticles were characterized and identified by UV–Vis, field emission scanning electron microscopy (FE‐SEM), transmission electron microscopy (TEM) and X‐ray diffraction (XRD). The antimicrobial activity of the CuS‐NPs and the ZnO/Zn(OH)2‐NPs were examined by broth dilution to determine the minimal inhibitory conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…For the system of this study the surface of ZnO crystals are expected to be very rich in Zn 2+ ions due to strong associations with NH 2 groups in the surrounding PEI (see Scheme ) and in accordance with the findings by Tang et al It is worth noting that the data in a report by Soria-Castro et al found that mixed Ca/Zn hydroxides displayed antimicrobial properties and suggested that Zn­(OH) 2 alone may not have such characteristics . Other authors found that mixed zinc oxide/zinc hydroxide nanoparticles exhibit antimicrobial activity against E. coli and S. aureus . For the interpretation of the results of this study it is propitious to consider also the findings of Malzahan et al on plasma-polymerized thin films deposited from zinc acetylacetonate in a low-pressure RF plasma reactor .…”
Section: Resultssupporting
confidence: 89%
“…For the system of this study the surface of ZnO crystals are expected to be very rich in Zn 2+ ions due to strong associations with NH 2 groups in the surrounding PEI (see Scheme ) and in accordance with the findings by Tang et al It is worth noting that the data in a report by Soria-Castro et al found that mixed Ca/Zn hydroxides displayed antimicrobial properties and suggested that Zn­(OH) 2 alone may not have such characteristics . Other authors found that mixed zinc oxide/zinc hydroxide nanoparticles exhibit antimicrobial activity against E. coli and S. aureus . For the interpretation of the results of this study it is propitious to consider also the findings of Malzahan et al on plasma-polymerized thin films deposited from zinc acetylacetonate in a low-pressure RF plasma reactor .…”
Section: Resultssupporting
confidence: 89%
“…326 Song et al 327 have shown an increase in production of ROS with an increase in quantity of ZnO nanoparticles. Khafri et al 328 have prepared ZnO nanoparticles for antibacterial and antifungal activity against Gram-positive ( Staphylococcus aureus) and Gram-negative (Klebsiella pneumonia and Acinetobacter baumannii) bacteria and fungi (Aspergillus oryzae). Their results for Klebsiella pneumonia, Acinetobacter baumannii, Escherichia coli, and Staphylococcus aureu bacteria gives MIC (minimal inhibitory concentration) of nearly 19.53, 9.77, 39.06, and 2.44 μg/mL, respectively.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…Khafri et al . have prepared ZnO nanoparticles for antibacterial and antifungal activity against Gram-positive (Staphylococcus aureus) and Gram-negative (Klebsiella pneumonia and Acinetobacter baumannii) bacteria and fungi (Aspergillus oryzae).…”
Section: Application Of Tm Znomentioning
confidence: 99%
“…Ultrasound processing is an environment-friendly, safe and inexpensive technology [21], used as a versatile tool in a wide range of scientific and technological applications, for instance: biology [22], chemistry [23], physics [24], medicine [25], material science [26], and industrial applications [27][28][29][30]. Nanomaterials can be obtained and modified using ultrasonic irradiation to assist synthetic methods in aqueous solution [31].…”
Section: Introductionmentioning
confidence: 99%